The incidence of healthcare use, ill health and mortality in adults with intellectual disabilities and mealtime support needs. (3rd November 2014) - Perez, C. M.; Ball, S. L.; Wagner, A. P.; Clare, I. C. H.; Holland, A. J.; Redley, M.
Abstract Background Adults with intellectual disabilities (ID) experience a wide range of eating, drinking and/or swallowing (EDS) problems, for which they receive diverse mealtime support interventions. Previous research has estimated that dysphagia (difficulty swallowing) affects 8% of all adults with ID and that 15% require some form of mealtime support. People with ID (whether they require mealtime support or not) also experience a greater burden of ill health and die younger than their peers in the general population with no ID. Methods Using an exploratory, population‐based cohort study design, we set out to examine health‐related outcomes in adults with ID who receive mealtime support for any eating, drinking or swallowing problem, by establishing the annual incidence of healthcare use, EDS‐related ill health, and all‐cause mortality. This study was conducted in two counties in the East of England. Results In 2009, 142 adults with mild to profound ID and a need for any type of mealtime support were recruited for a baseline survey. At follow‐up 1 year later, 127 individuals were alive, eight had died and seven could not be contacted. Almost all participants had one or more consultations with a general practitioner (GP) each year (85–95%) and, in the first year, 20% reportedly had one or more emergency hospitalizations. Although their annual number of GP visits was broadly comparable with that of the general population, one‐fifth of this population's primary healthcare use was directly attributable to EDS‐related ill health. Respiratory infections were the most common cause of morbidity, and the immediate cause of all eight deaths, while concerns about nutrition and dehydration were surprisingly minor. Our participants had a high annual incidence of death (5%) and, with a standardized mortality ratio of 267, their observed mortality was more than twice that expected in the general population of adults with ID (not selected because of mealtime support for EDS problems). Conclusions All Annual Health Checks now offered to adults with ID should include questions about respiratory infections and EDS functioning, in order to focus attention on EDS problems in this population. This has the potential to reduce life‐threatening illness.